Genetic Parameter Estimation of Rambutan Seedling Morphologicaltraits For A Better Rootstock Performance - Panjisakti Basunanda; Siswandono Siswandono; Nasrullah Nasrullah (Jurnal Ilmu Pertanian, 2000)
-